1994
DOI: 10.1002/mrm.1910320114
|View full text |Cite
|
Sign up to set email alerts
|

Dual interleaved 1H and proton‐decoupled‐31P in Vivo chemical shift imaging of human brain

Abstract: A technique is demonstrated to obtain interleaved proton (1H) and 1H-decoupled phosphorus (31P) spectra of human brain using 2D CSI. A modified commercial full-body imager and a dual-tuned birdcage head-coil were employed. Because proton relaxation times are shorter than those of phosphorus, TR(1H) can be chosen to be shorter than TR(31P), thus permitting a 1H acquisition to be inserted in each 31P cycle. The scheme results in significant time savings as both CSI data sets are obtained concurrently with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Nonproton, or X-nuclear, studies give access to information not available from proton detection alone. For example, 31 P is used to investigate metabolism via high energy phosphates (1,2), 13 C provides information about glucose and glycogen metabolism (3)(4)(5), and 23 Na may be used to assess the viability of healthy and tumorous tissue (6)(7)(8) or cartilage defects (9).…”
Section: Introductionmentioning
confidence: 99%
“…Nonproton, or X-nuclear, studies give access to information not available from proton detection alone. For example, 31 P is used to investigate metabolism via high energy phosphates (1,2), 13 C provides information about glucose and glycogen metabolism (3)(4)(5), and 23 Na may be used to assess the viability of healthy and tumorous tissue (6)(7)(8) or cartilage defects (9).…”
Section: Introductionmentioning
confidence: 99%
“…Refocused insensitive nucleus enhancement by polarization transfer (RINEPT) (Gonen et al , 1997)) or acquisition schemes (e.g. dual interleaved acquisition of 1 H and 31 P CSI (Gonen et al , 1994), may be useful in increasing SNR and reducing measurement times. Recent studies focusing on applying compressed sensing (Candes et al , 2006) to MRI (Lustig et al , 2008) and MRS (von Morze et al , 2012) are exciting and may improve temporal and spatial resolution significantly with the potential of making 31 P MRSI more clinically applicable in the future.…”
Section: 0 Preclinical 31p Mr Spectroscopy Of Solid Tumorsmentioning
confidence: 99%
“…itate all of these 1 H requirements during a 31 P study, our team designed several doublee-tuned RF antennas with highly sensitive 31 P and 1 H channels. Moreover, with these double-tuned antennas, 31 P and 1 H spectroscopy can be carried simultaneously, thereby minimizing adjustment and image requirements [15][16][17]. A comparison of the double-tuned probes with conven-tional, single-tuned ones showed that, despite double tuning, there is no significant loss in 31 P sensitivity when the 1 H channel provides the needed performance.…”
Section: T)mentioning
confidence: 99%